Soft Switched Multi-Output Flyback Converter with Voltage Doubler - K. Deepa; Hridya Merin Saju; M. Vijaya Kumar (Institute of Advanced Engineering and Science, 2015)
A novel multi-output voltage doubler circuit with resonant switching technique is proposed in this paper. The resonant topology in the primary side of the flyback transformer switches the device either at zero voltage or current thus optimizing the switching devices by mitigating the losses. The voltage doubler circuit introduced in the load side increases the voltage by twice the value thereby increasing the load power and density. The proposed Multi-output Isolated Converter removes the need for mutiple SMPS units for a particular application. This reduces the size and weight of the converters considerably leading to a greater payload. This paper aims at optimizing the proposed converter with some design changes. The results obtained from the hardware prototype are given in a comprehensive manner for a 3.5W converter operating at output voltages of 5V and 3.3V at 50 kHz switching frequency. The converter output is regulated with the PI controller designed with SG3523 IC. The effects of load and line regulation for ±20% variations are analyzed in detail.